Layered oxide positive electrode material, preparation method thereof, positive electrode composition, sodium ion secondary battery and application

By regulating the composition and process of layered oxide positive electrode materials, the problems of insufficient performance and high cost of sodium ion secondary battery positive electrode materials are solved, and a layered oxide positive electrode material with excellent performance and low cost are prepared, suitable for new energy sources Energy storage applications.

CN119133428APending Publication Date: 2024-12-13LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411357218.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing sodium ion secondary battery positive electrode materials have shortcomings in the initial discharge specific capacity, rate performance and cycling performance, and are relatively expensive, making it difficult to meet the new energy industry's demand for low-cost and high-performance materials.

Method used

Develop a layered oxide positive electrode material with the general formula of Naa(CubTi1-b)x(NicMn1-c)yM1-x-yOd, by regulating the ratio of Cu and Ti, the ratio of Ni and Mn, spherical degree and other factors. , a material with excellent initial discharge specific capacity, rate performance and cycle performance was prepared, and a simple sintering process was used to reduce costs.

Benefits of technology

The layered oxide cathode material with low cost and excellent performance was successfully prepared, with high initial discharge specific capacity, good rate performance and cycling performance. It is suitable for sodium ion secondary batteries and meets the needs of new energy energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133428A_ABST
    Figure CN119133428A_ABST
Patent Text Reader

Abstract

The invention relates to a layered oxide positive electrode material, the general formula of the layered oxide positive electrode material is Naa (CubTi1-b) x (NicMn1-c) yM1-x-yOd, a, b, c, d, x, y and M have meanings defined in the specification, an XRD spectrogram of the layered oxide positive electrode material does not have a copper oxide impurity peak and a nickel oxide impurity peak, the sphericity degree of the layered oxide positive electrode material is greater than or equal to 0.85, and the residual alkali content of the layered oxide positive electrode material is less than or equal to 0.65%. The sodium ion secondary battery adopting the positive electrode material disclosed by the invention has relatively high initial discharge specific capacity and excellent rate capability and cycle performance. The invention also relates to a method for preparing the positive electrode material, a positive electrode composition containing the positive electrode material, a sodium ion secondary battery and application of the sodium ion secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of energy storage technology, in particular to the field of sodium ion secondary batteries. Specifically, the present invention relates to a layered oxide positive electrode material, a preparation method thereof, a positive electrode composition comprising the layered oxide positive electrode material, a sodium ion secondary battery comprising the positive electrode composition, and uses of the sodium ion secondary battery. Background Art

[0002] In recent years, lithium-ion secondary batteries have developed strongly in the field of new energy, but the low reserves and uneven distribution of lithium resources have restricted the development of lithium-ion secondary batteries in industries such as grid energy storage and electric vehicles. As a "substitute" for lithium-ion secondary batteries, sodium-ion secondary batteries have many advantages, such as abundant resources, uniform distribution, and low cost (theoretically as low as 0.2~0.4 yuan per watt-hour). As competition in the new energy industry becomes increasingly fierce, people are paying more and more attention to low-cost sodium-ion secondary batteries. As an important component of sodium-ion secondary batteries, the cost of positive electrode materials is an important part of determining the cost of secondary batteries. On the other hand, people have higher and higher requirements for the performance of secondary batteries, such as initial discharge specific capacity, rate performance, and cycle performance. Therefore, it is imperative to prepare high-performance and low-cost positive electrode materials.

[0003] In view of the above problems, technicians in this field need to develop a new sodium ion secondary battery positive electrode material, which has a higher initial discharge specific capacity, good rate performance and cycle performance, and has cost advantages. Summary of the invention

[0004] The present invention is made in view of the above problems existing in the prior art.

[0005] In a first aspect, the present invention relates to a layered oxide positive electrode material having the general formula:

[0006] Na a (Cu b Ti 1-b ) x (Ni c Mn 1-c ) y M 1-x-y O d

[0007] Wherein 0.65≤a≤1.00, preferably 0.75≤a≤1.00, preferably 0.80≤a≤1.00, more preferably 0.95≤a≤1.00; 0.45≤b≤0.55, preferably 0.45≤b≤0.50; 0.33≤c≤0.50, preferably 0.35≤c≤0.50, preferably 0.40≤c≤0.50, more preferably 0.45≤c≤0.50; 1.60≤d≤2.40; 0<x≤0.20, 0.70≤y<1.00, more preferably 0. 78≤y≤0.99, and 0.80≤x+y≤1.00, preferably 0.90≤x+y≤1.00, more preferably 0.98≤x+y≤1.00; M is selected from one or more of Fe, Mg, Zr, Zn, Al, Ca, Li, Ba, V, Cr, Mo, Co, Bi, B, Si, and P, preferably one or more of Fe, Co, Mg, Ba, Mo, Zr, Al, Ca, B, and P, and the values ​​of the subscripts of the elements in the general formula are selected so that the general formula satisfies the valence balance; and

[0008] wherein 0.28≤bx+cy≤0.50, preferably 0.40≤bx+cy≤0.50, more preferably 0.44≤bx+cy≤0.50,

[0009] The XRD spectrum of the layered oxide positive electrode material does not contain copper oxide impurity peaks and nickel oxide impurity peaks;

[0010] The sphericity of the layered oxide positive electrode material is Φ≥0.85; and

[0011] Wherein, based on the total weight of the layered oxide positive electrode material, the residual alkali content of the layered oxide positive electrode material is ≤0.65%, preferably ≤0.50%, and more preferably ≤0.30%.

[0012] The present invention successfully obtains a layered oxide positive electrode material with excellent initial discharge capacity, rate performance and cycle performance, and low cost by regulating the composition of the positive electrode material of the sodium ion secondary battery and the stoichiometric relationship of the constituent elements, such as the total content of Cu and Ti, the total content of Ni and Mn, the ratio of Cu or Ti to Cu+Ti (or the ratio of Cu to Ti), the ratio of Ni or Mn to Ni+Mn (or the ratio of Ni to Mn), the total content of Cu and Ni, and the sphericity of the layered oxide positive electrode material. The layered oxide positive electrode material prepared by the present invention has a uniform composition, and there are no impurity peaks of CuO, NiO, etc. in the XRD spectrum of the product, and the layered oxide positive electrode material prepared by the present invention has a low residual alkali content, which is conducive to improving the electrochemical properties of the layered oxide positive electrode material. In addition, after research, the inventors also found that by further regulating the ratio of Cu / Ni and / or Cu / Mn, the content of each element, etc., the initial discharge capacity, rate performance or cycle performance can be further improved, so as to better meet market demand.

[0013] In a second aspect, the present invention relates to a method for preparing the layered oxide positive electrode material according to the first aspect of the present invention, comprising the following steps:

[0014] (1) Provide a NiMn precursor having a Ni / Mn molar ratio satisfying c / (1-c): a sphericity of Φ ≥ 0.90, and a volume average particle size D v 50 is 3.0-15.0 µm, wherein c has the meaning defined above;

[0015] (2) Do any of the following:

[0016] (i) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, and optionally cooling and crushing;

[0017] (ii) mixing the sodium source, the NiMn precursor, the copper source, the titanium source, and a portion of the optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, cooling and pulverizing the resulting product, and then adding the remaining portion of the optional M source, mixing uniformly, and sintering again at 800-950° C. for 15-25 hours, and optionally cooling and pulverizing; or

[0018] (iii) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source, and sintering the mixture at 800-950° C. for 15-25 hours, cooling and crushing the resulting mixture, and sintering the mixture again at 800-950° C. for 15-25 hours, and optionally cooling and crushing the mixture,

[0019] wherein Na, Ni, Mn, Cu, Ti and optionally M meet the stoichiometric ratios defined above, and wherein the volume average particle size D of the NiMn precursor v 50≥2×(the largest volume average particle size D among the copper source, the titanium source and the M source) v 50).

[0020] The preparation method of the present invention uses a NiMn precursor with high sphericity, and then mixes it with a source of Na, Cu, Ti and an optional doping element M, and controls the ratio of the volume average particle size of the NiMn precursor to the source of Cu, Ti and an optional doping element M, as well as the temperature and time of the sintering process, to successfully prepare a sodium ion secondary battery positive electrode material with excellent initial discharge specific capacity, rate performance and cycle performance. The preparation method of the present invention is simple to operate, has a wide range of raw material sources, and has cost advantages.

[0021] In a third aspect, the present invention relates to a positive electrode composition, which comprises the layered oxide positive electrode material according to the first aspect of the present invention.

[0022] In a fourth aspect, the present invention relates to a sodium ion secondary battery, comprising the positive electrode composition according to the third aspect of the present invention.

[0023] In a fifth aspect, the present invention relates to the use of the sodium ion secondary battery of the fourth aspect of the present invention in an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solution of the present invention, the following will briefly describe the drawings required for describing the embodiments. It should be understood that these drawings are only for the convenience of technicians to understand the present invention more easily, and are not intended to limit the scope of the present invention.

[0025] Figure 1 This is a scanning electron microscope image of the layered oxide positive electrode material according to Example 1 of the present invention.

[0026] Figure 2 This is a scanning electron microscope image of the layered oxide positive electrode material according to Example 2 of the present invention.

[0027] Figure 3 This is a scanning electron microscope image of the layered oxide positive electrode material according to Example 4 of the present invention.

[0028] Figure 4 1 is the XRD spectrum of the layered oxide positive electrode material according to Examples 3, 5 and 6 of the present invention.

[0029] Figure 5 1 and 2. The XRD spectra of the layered oxide positive electrode materials according to Examples 2 and 7 of the present invention, and Comparative Examples 7, 9 and 11. DETAILED DESCRIPTION

[0030] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.

[0031] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.

[0032] The present invention relates to a layered oxide positive electrode material, a preparation method thereof, a positive electrode composition comprising the layered oxide positive electrode material, a sodium ion secondary battery comprising the positive electrode composition, and use of the sodium ion secondary battery.

[0033] The present invention will be described in detail below.

[0034] Layered oxide cathode materials

[0035] In a first aspect, the present invention relates to a layered oxide positive electrode material having the general formula:

[0036] Na a (Cu b Ti 1-b ) x (Ni c Mn 1-c ) y M 1-x-y O d

[0037] Wherein 0.65≤a≤1.00, preferably 0.75≤a≤1.00, preferably 0.80≤a≤1.00, more preferably 0.95≤a≤1.00; 0.45≤b≤0.55, preferably 0.45≤b≤0.50; 0.33≤c≤0.50, preferably 0.35≤c≤0.50, preferably 0.40≤c≤0.50, more preferably 0.45≤c≤0.50; 1.60≤d≤2.40; 0<x≤0.20, 0.70≤y<1.00, more preferably 0. 78≤y≤0.99, and 0.80≤x+y≤1.00, preferably 0.90≤x+y≤1.00, more preferably 0.98≤x+y≤1.00; M is selected from one or more of Fe, Mg, Zr, Zn, Al, Ca, Li, Ba, V, Cr, Mo, Co, Bi, B, Si, and P, preferably one or more of Fe, Co, Mg, Ba, Mo, Zr, Al, Ca, B, and P, and the values ​​of the subscripts of the elements in the general formula are selected so that the general formula satisfies the valence balance; and

[0038] wherein 0.28≤bx+cy≤0.50, preferably 0.40≤bx+cy≤0.50, more preferably 0.44≤bx+cy≤0.50,

[0039] The XRD spectrum of the layered oxide positive electrode material does not contain copper oxide impurity peaks and nickel oxide impurity peaks;

[0040] The sphericity of the layered oxide positive electrode material is Φ≥0.85; and

[0041] Wherein, based on the total weight of the layered oxide positive electrode material, the residual alkali content of the layered oxide positive electrode material is ≤0.65%, preferably ≤0.50%, and more preferably ≤0.30%.

[0042] The present invention successfully obtains a layered oxide positive electrode material with excellent initial discharge capacity, rate performance and cycle performance, and low cost by regulating the composition of the positive electrode material of the sodium ion secondary battery and the stoichiometric relationship of the constituent elements, such as the total content of Cu and Ti, the total content of Ni and Mn, the ratio of Cu or Ti to Cu+Ti (or the ratio of Cu to Ti), the ratio of Ni or Mn to Ni+Mn (or the ratio of Ni to Mn), the total content of Cu and Ni, and the sphericity of the layered oxide positive electrode material. The layered oxide positive electrode material prepared by the present invention has a uniform composition, and there are no impurity peaks of CuO, NiO, etc. in the XRD spectrum of the product, and the layered oxide positive electrode material prepared by the present invention has a low residual alkali content, which is conducive to improving the electrochemical properties of the layered oxide positive electrode material. In addition, after research, the inventors also found that by further regulating the ratio of Cu / Ni and / or Cu / Mn, the content of each element, etc., the initial discharge capacity, rate performance or cycle performance can be further improved, so as to better meet market demand.

[0043] In the general formula of the layered oxide positive electrode material of the present invention, the subscript a of the sodium element is in the range of 0.65≤a≤1.00, preferably 0.75≤a≤1.00, preferably 0.80≤a≤1.00, and more preferably 0.95≤a≤1.00. As an example, a can be 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, or within the range defined by any two of them.

[0044] In the general formula of the layered oxide positive electrode material of the present invention, the range of the subscript b for the copper element is 0.45≤b≤0.55. When b is within the above range, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance. Preferably, when 0.45≤b≤0.50, within this preferred range, it will be beneficial to further improve the initial discharge specific capacity and / or rate performance. As an example, b may be 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, or within the range defined by any two of them. Similarly, the range of the subscript 1-b for the titanium element is 0.45≤1-b≤0.55, for example, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, or the range defined by any two of them.

[0045] In the general formula of the layered oxide positive electrode material of the present invention, the range of the subscript c for the nickel element is 0.33≤c≤0.50. When c is within the above range, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance. Preferably, 0.35≤c≤0.50, preferably 0.40≤c≤0.50, and more preferably 0.45≤c≤0.50. When c is within the defined range, it is beneficial to further improve the initial discharge specific capacity and / or rate performance corresponding to the obtained layered oxide positive electrode material. As an example, c may be 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, or within the range defined by any two of them. Similarly, the range of the subscript 1-c of manganese is 0.50≤1-c≤0.67, preferably 0.50≤1-c≤0.65, preferably 0.50≤1-c≤0.60, and more preferably 0.50≤1-c≤0.55. As an example, 1-c can be 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, or the range defined by any two of them.

[0046] In the general formula of the layered oxide positive electrode material of the present invention, the range of the subscript d of the oxygen element is 1.60≤d≤2.40. It is easy for those skilled in the art to understand that the subscript of the oxygen element actually depends on the composition of other elements in the layered oxide positive electrode material, and the subscript value of the oxygen element makes the layered oxide positive electrode material of the present invention satisfy the valence balance. As an example, d can be 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, or within the range defined by any two of them. It should be noted that in this application, including in the embodiments, sometimes for convenience, the subscript of O is directly recorded as "2". Those skilled in the art can understand that this is a commonly used simple notation in the art, and the specific subscript of O can be easily determined by those skilled in the art based on specific raw material composition and other conditions.

[0047] In the general formula of the layered oxide positive electrode material of the present invention, the range of the subscript x for the copper element and the titanium element is 0<x≤0.20, for example, 0.01≤x≤0.20. It is easy for those skilled in the art to understand that x actually represents the sum of the contents of Cu and Ti. The inventors found in the study that when the sum of the contents of Cu and Ti is within a limited range, Cu and Ti can better play their respective advantages, and the resulting layered oxide positive electrode material has improved initial discharge specific capacity, rate performance and / or cycle performance. As an example, x may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or within the range defined by any two of them.

[0048] Similarly, in the general formula of the layered oxide positive electrode material of the present invention, the range of the subscript y for the nickel element and the manganese element is 0.70≤y<1.00, for example, 0.70≤y≤0.99, more preferably 0.78≤y≤0.99. It is easy for those skilled in the art to understand that y actually represents the sum of the contents of Ni and Mn. When y is within the range defined in the present invention, the initial discharge capacity, rate performance and / or cycle performance of the obtained layered oxide positive electrode material are further improved. As an example, y may be 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or within the range defined by any two of them.

[0049] In the general formula of the layered oxide positive electrode material of the present invention, the subscript x about the copper element and the titanium element and the subscript y about the nickel element and the manganese element satisfy: 0.80≤x+y≤1.00, preferably 0.90≤x+y≤1.00, and more preferably 0.98≤x+y≤1.00. As an example, x+y may be 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, or within the range defined by any two of them.

[0050] In the general formula of the layered oxide positive electrode material of the present invention, the doping element M can be selected from one or more of Fe, Mg, Zr, Zn, Al, Ca, Li, Ba, V, Cr, Mo, Co, Bi, B, Si, and P, preferably one or more of Fe, Co, Mg, Ba, Mo, Zr, Al, Ca, B, and P. The content of the doping element M may be 1-xy. In some embodiments, the content of the doping element M is in the range of 0-0.20, for example, 0.02-0.18. As an example, the content of the doping element M may be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or in the range defined by any two of them.

[0051] In some embodiments, the layered oxide cathode material of the present invention is doped with multiple doping elements at the same time. The doping amount of each specific doping element in the doping element M represented by the subscript in the general formula of the layered oxide cathode material of the present invention (hereinafter the same) can be in the range of 0-0.20, for example, 0.02-0.18, and the sum of M is in the range of 0-0.20. As an example, when doping with Fe element, the doping amount of Fe element can be 0-0.20, for example, 0.02-0.18, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or within the range defined by any two of them; when doping with Mg element, the doping amount of Mg element can be 0.05-0.20, for example, 0.08-0.18, for example, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or within the range defined by any two of them. 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or within the range defined by any two of them; when doped with Al element, the doping amount of Al element can be 0-0.15, for example, 0-0.10, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or within the range defined by any two of them; when doped with Al element, the doping amount of Al element can be 0-0.15, for example, 0-0.10, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or within the range defined by any two of them; When Ca element is doped, the doping amount of Ca element can be 0-0.12, for example, 0-0.10, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, or within the range defined by any two of them; when Zr element is doped, the doping amount of Zr element can be 0-0.20, for example, 0-0.10, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or the range defined by any two of them; when doped with Zn element, the doping amount of Zn element can be 0-0.18, for example, 0-0.12, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, or the range defined by any two of them; when doped with B element, the doping amount of B element can be 0-0.15, for example, 0-0.10, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or within the range defined by any two of them; when doped with P element, the doping amount of P element can be 0-0.20, for example, 0.05-0.15, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0 .18, 0.19, 0.20, or the range defined by any two of them; similarly, when doping Li, Ba, V, Cr, Mo, Co, Bi, Si, etc., the doping amount of Li, Ba, V, Cr, Mo, Co, Bi, Si, etc. can be 0-0.20, such as 0.05-0.15, such as 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or the range defined by any two of them. .

[0052] In the general formula of the layered oxide positive electrode material of the present invention, the subscript of the copper element and the subscript of the nickel element satisfy 0.28≤bx+cy≤0.50. When bx+cy is within the above range, it helps to improve the initial discharge capacity, rate performance and / or cycle performance of the layered oxide positive electrode material. Preferably, 0.40≤bx+cy≤0.50, more preferably 0.44≤bx+cy≤0.50, within the preferred and more preferred range, it is conducive to further improving the initial discharge capacity and / or rate performance. As an example, bx+cy may be 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, or within the range defined by any two of them.

[0053] There are no copper oxide miscellaneous peaks and nickel oxide miscellaneous peaks in the XRD spectrum of the layered oxide positive electrode material of the present invention. The inventors have found through research that under the same conditions, the presence of copper oxide miscellaneous peaks and nickel oxide miscellaneous peaks will deteriorate the initial discharge specific capacity, rate performance and / or cycle performance of the layered oxide positive electrode material. Whether copper oxide and nickel oxide miscellaneous peaks are present in the XRD spectrum is mainly related to the composition and composition uniformity of the layered oxide positive electrode material. For example, when the preparation conditions of the layered oxide positive electrode material, such as elemental composition and stoichiometric relationship, such as the total content of Cu and Ti, the total content of Ni and Mn, the ratio of Cu or Ti to Cu+Ti (or the ratio of Cu to Ti), the ratio of Ni or Mn to Ni+Mn (or the ratio of Ni to Mn), and the total content of Cu and Ni meet the range defined by the present invention, it is beneficial to improve the composition uniformity of the layered oxide positive electrode material. The XRD test can be carried out by conventional test methods in the art, for example, it can be tested by conventional test methods in the art with the aid of BrukerD8 ADVANCE (angle reproducibility, such as 0.0001°, angle resolution, such as 0.02°).

[0054] In the present application, “no copper oxide miscellaneous peak and nickel oxide miscellaneous peak” means that the intensity of the copper oxide miscellaneous peak and the nickel oxide miscellaneous peak is lower than the detection limit of the XRD measurement equipment, which can be easily understood by those skilled in the art.

[0055] In the layered oxide positive electrode material of the present invention, the residual alkali content is ≤0.65%, preferably ≤0.50%, and more preferably ≤0.30%, based on the total weight of the layered oxide positive electrode material. The term "residual alkali" refers to sodium carbonate and sodium hydroxide on the surface of the prepared layered oxide positive electrode material. The inventors found in the study that under the same conditions, when the residual alkali content is greater than the range defined in the present invention, the initial discharge capacity, rate performance and / or cycle performance of the layered oxide positive electrode material will be deteriorated. The residual alkali content is mainly related to the composition and composition uniformity of the layered oxide positive electrode material. After research, the inventors found that when the preparation conditions of the layered oxide positive electrode material, such as elemental composition and stoichiometric relationship, such as the total content of Cu and Ti, the total content of Ni and Mn, the ratio of Cu or Ti to Cu+Ti (or the ratio of Cu to Ti), the ratio of Ni or Mn to Ni+Mn (or the ratio of Ni to Mn), and the total content of Cu and Ni are within the range defined in the present invention, it is conducive to obtaining a product with a lower residual alkali content. As an example, the residual alkali content of the layered oxide positive electrode material of the present invention may be ≤0.65%, ≤0.60%, ≤0.55%, ≤0.50%, ≤0.45%, ≤0.40%, ≤0.35%, ≤0.30%, ≤0.25%, ≤0.20%, ≤0.15%, ≤0.10%, ≤0.05%, ≤0.03%, or 0%.

[0056] The inventors have found that when the content relationship of each element in the general formula of the layered oxide positive electrode material of the present invention satisfies one or more of the following conditions, one or more of the initial discharge specific capacity, rate performance or cycle performance of the obtained layered oxide positive electrode material can be further improved.

[0057] In some embodiments, the ratio of the copper content bx to the nickel content cy is in the range of 0.010-0.350, preferably 0.010-0.320, and more preferably 0.010-0.260. As an example, bx / cy may be 0.010, 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, 0.100, 0.110, 0.120, 0.130, 0.140, 0.150, 0.160, 0.170, 0.180, 0.190, 0.200, 0.210, 0.220, 0.230, 0.240, 0.250, 0.260, 0.270, 0.280, 0.290, 0.300, 0.310, 0.320, 0.330, 0.340, 0.350, or a range defined by any two of them.

[0058] In some embodiments, the ratio of the copper content bx to the manganese content (1-c)y is in the range of 0.005-0.300, preferably 0.010-0.260. As an example, bx / (1-c)y may be 0.005, 0.010, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, 0.070, 0.075, 0.080, 0.085, 0.090, 0.095, 0.100, 0.105, 0.110, 0.115, 0.120, 0.125, 0.130, 0.135, 0.140, 0.145, 0.150, 0.260, 0.265, 0.270, 0.275, 0.280, 0.285, 0.290, 0.295, 0.300, or the range defined by any two of them.

[0059] In the general formula of the layered oxide positive electrode material of the present invention, the content of copper element is bx. As an example, bx is in the range of 0.005-0.110, more preferably 0.005-0.100. For example, bx can be 0.005, 0.010, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, 0.070, 0.075, 0.080, 0.085, 0.090, 0.095, 0.100, 0.105, 0.110, or in the range defined by any two of them.

[0060] Similarly, in the general formula of the layered oxide positive electrode material of the present invention, the content of titanium element is (1-b)x. In some embodiments, (1-b)x is in the range of 0.005-0.110, more preferably 0.005-0.100. For example, (1-b)x can be 0.005, 0.010, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, 0.070, 0.075, 0.080, 0.085, 0.090, 0.095, 0.100, 0.105, 0.110, or in the range defined by any two of them.

[0061] Similarly, in the general formula of the layered oxide positive electrode material of the present invention, the content of nickel element is cy. In some embodiments, cy is in the range of 0.250-0.500, preferably 0.320-0.500, preferably 0.350-0.500, more preferably 0.390-0.500. For example, cy can be 0.250, 0.255, 0.260, 0.265, 0.270, 0.275, 0.280, 0.285, 0.290, 0.295, 0.300, 0.305, 0.310, 0.315, 0.320, 0.325, 0.330, 0.335, 0.340, 0.345, 0.350, 0.355, 0.360, 0.365, 0.370, 0.375, 0.380, 0.385, 0.390, 0.395, 0.40 ... 490, 0.495, 0.500, or the range defined by any two of them.

[0062] Similarly, the content of manganese element is (1-c)y. In some embodiments, (1-c)y is in the range of 0.350-0.700, preferably 0.350-0.500, more preferably 0.390-0.500. For example, (1-c)y can be 0.350, 0.355, 0.360, 0.365, 0.370, 0.375, 0.380, 0.385, 0.390, 0.395, 0.400, 0.405, 0.410, 0.415, 0.420, 0.425, 0.430, 0.435, 0.440, 0.445, 0.450, 0.455, 0.460, 0.465, 0.470, 0.475, 0.480, 0.485, 0.490, 0.495, 0.500, 0.505, 0.510, 0.515, 0.520, 0.525, 0.540, 0.545, 0.550, 0.555, 0.560, 0.565, 0.570, 0.575, 0.580, 0.585, 0.590, 0.595, 0.600, 0.605, 0.610, 0.615, 0.620, 0.625, 0.630, 0.635, 0.640, 0.645, 0.650, 0.655, 0.660, 0.665, 0.670, 0.675, 0.680, 0.685, 0.690, 0.695, 0.700, or the range defined by any two of them.

[0063] In some embodiments, the tap density TD (tap density) of the layered oxide cathode material of the present invention is 1.80-2.10 g / cm 3 , preferably 1.90-2.10 g / cm 3 In the present invention, "tap density" has the meaning generally understood in the art. The term "tap density" refers to the mass per unit volume measured after the powder in a container is tapped under specified conditions. For the measurement method of the tap density, see the measurement method section of the embodiment. As an example, the tap density of the layered oxide positive electrode material of the present invention is 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10 g / cm 3 , or within the range defined by any two of them.

[0064] In some embodiments, the sphericity of the layered oxide positive electrode material of the present invention is Φ≥0.85, preferably Φ≥0.90. In the present invention, the sphericity refers to the ratio of the shortest diameter passing through the center of the layered oxide positive electrode material particle to the longer diameter in the direction perpendicular to the shortest diameter in the plane presented by the SEM image of the layered oxide positive electrode material. As an example, the sphericity Φ of the layered oxide positive electrode material of the present invention may be 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, or within the range defined by any two of them.

[0065] In some embodiments, the volume average particle size D of the layered oxide positive electrode material of the present invention is v 50 is in the range of 3.0-15.0 μm, preferably 4.0-14.0 μm, more preferably 6.0-8.0 μm. When the volume average particle size D of the layered oxide positive electrode material is v When D is within the above range, the initial discharge capacity, rate performance and cycle performance are further improved. v The 50 particle size refers to the particle size that is smaller than this particle size value and the particle size that is larger than this particle size value in the volume cumulative distribution curve, each accounting for 50% of the total sample volume. v The particle size can be measured by conventional testing methods in the art, such as laser diffraction. As an example, the volume average particle size D of the layered oxide positive electrode material is v 50 may be 3.00, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 7.50, 8.00, 8.50, 9.00, 9.50, 10.00, 10.50, 11.00, 11.50, 12.00, 12.50, 13.00, 13.50, 14.00, 14.50, 15.00 μm, or the range defined by any two of them.

[0066] In some embodiments, the layered oxide positive electrode material of the present invention is a P2 phase or an O3 phase, or a mixed phase of a P2 phase and an O3 phase, preferably an O3 phase.

[0067] In some embodiments, the layered oxide cathode material of the present invention is a secondary spherical polycrystalline material.

[0068] Preparation method of layered oxide positive electrode material

[0069] The second aspect of the present invention provides a method for preparing a layered oxide positive electrode material according to the first aspect of the present invention, comprising the following steps:

[0070] (1) Provide a NiMn precursor having a Ni / Mn molar ratio satisfying c / (1-c): a sphericity of Φ ≥ 0.90, and a volume average particle size D v 50 is 3.0-15.0 µm, wherein c has the meaning defined above;

[0071] (2) Do any of the following:

[0072] (i) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, and optionally cooling and crushing;

[0073] (ii) mixing the sodium source, the NiMn precursor, the copper source, the titanium source, and a portion of the optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, cooling and pulverizing the resulting product, and then adding the remaining portion of the optional M source, mixing uniformly, and sintering again at 800-950° C. for 15-25 hours, and optionally cooling and pulverizing; or

[0074] (iii) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source, and sintering the mixture at 800-950° C. for 15-25 hours, cooling and crushing the resulting mixture, and sintering the mixture again at 800-950° C. for 15-25 hours, and optionally cooling and crushing the mixture,

[0075] wherein Na, Ni, Mn, Cu, Ti and optionally M meet the stoichiometric ratios defined above, and wherein the volume average particle size D of the NiMn precursor v 50≥2×(the largest volume average particle size D among the copper source, the titanium source and the M source) v 50).

[0076] As a common positive electrode material in the field of secondary batteries, nickel-cobalt-manganese ternary positive electrode materials mostly use nickel-cobalt-manganese hydroxide prepared by coprecipitation as a precursor, and ammonia water is used as a complexing agent to control crystallization under a protective atmosphere, and then mixed with a lithium source for sintering. However, when preparing the positive electrode material of sodium-ion secondary batteries with reference to nickel-cobalt-manganese ternary positive electrode materials, it faces many difficulties. One reason is that the positive electrode materials of sodium-ion secondary batteries mostly use cheap metals such as copper, titanium, iron, and manganese, but in the presence of ammonia water, copper easily forms copper-ammine complexes, resulting in coprecipitation failure. In addition, the pH of trivalent iron ion precipitation is low, and it is easy to precipitate before other metals, resulting in uneven distribution of coprecipitated materials, which directly affects electrochemical performance. On the other hand, if the positive electrode material of sodium-ion secondary batteries is prepared by dry mixing process directly using oxides according to the prior art, the uniformity of the obtained positive electrode material of sodium-ion secondary batteries is relatively poor.

[0077] The preparation method of the present invention uses a NiMn precursor with a high sphericity, and then mixes it with a source of Na, Cu, Ti and an optional doping element M, and controls the ratio of the volume average particle size of the NiMn precursor to the source of Cu, Ti and an optional doping element M, and the temperature and time of the sintering process, and successfully obtains a sodium ion secondary battery positive electrode material with excellent initial discharge specific capacity, rate performance and cycle performance. The layered oxide positive electrode material obtained by the method of the present invention has a uniform composition and a high sphericity, and there are no copper oxide impurity peaks and nickel oxide impurity peaks in the XRD spectrum of the product, and the residual alkali content of the obtained product is low. In addition, the preparation method of the present invention is simple to operate, has a wide source of raw materials, and has cost advantages.

[0078] Each step is described in detail below.

[0079] Step (1)

[0080] In step (1), a NiMn precursor having a molar ratio of Ni / Mn satisfying c / (1-c) is provided, wherein the sphericity thereof is Φ≥0.90, and the volume average particle size D v 50 is 3.0-15.0 µm, wherein c has the meaning defined above.

[0081] In the method of the present invention, the NiMn precursor used has a higher sphericity. In some embodiments, the sphericity of the NiMn precursor is Φ≥0.90. For example, Φ may be 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, or within the range defined by any two of them. The inventors found in the study that by using a NiMn precursor with a higher sphericity and comprehensively regulating the composition of the layered oxide positive electrode material, the proportional relationship of the volume average particle size of the source material, etc., the obtained layered oxide positive electrode material also has a higher sphericity. In addition, the inventors also found in the study that the use of a NiMn precursor with a sphericity of Φ≥0.90 is beneficial to improving the composition uniformity of the obtained layered oxide positive electrode material and reducing the residual alkali content.

[0082] In some embodiments, the volume average particle size D of the NiMn precursor is v 50 is 3.0-15.0µm. As an example, the D vThe particle size may be 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0 μm, or within the range defined by any two of them.

[0083] In some embodiments, the NiMn precursor is selected from one or more of the following compounds: NiMn hydroxide, NiMn oxide, NiMn carbonate, wherein the stoichiometric ratio of Ni to Mn is c / (1-c), wherein c has the meaning defined above.

[0084] Step (2)

[0085] In step (2), perform any of the following:

[0086] (i) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, and optionally cooling and crushing;

[0087] (ii) mixing the sodium source, the NiMn precursor, the copper source, the titanium source, and a portion of the optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, cooling and pulverizing the resulting product, and then adding the remaining portion of the optional M source, mixing uniformly, and sintering again at 800-950° C. for 15-25 hours, and optionally cooling and pulverizing; or

[0088] (iii) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source, and sintering the mixture at 800-950° C. for 15-25 hours, cooling and crushing the resulting mixture, and sintering the mixture again at 800-950° C. for 15-25 hours, and optionally cooling and crushing the mixture,

[0089] wherein Na, Ni, Mn, Cu, Ti and optionally M meet the stoichiometric ratios defined above, and wherein the volume average particle size D of the NiMn precursor v 50≥2×(the largest volume average particle size D among the copper source, the titanium source and the M source) v 50).

[0090] The sintering process of the present invention can adopt a primary sintering process or a secondary sintering process. In the primary sintering process, after all materials are mixed evenly, a primary sintering process is performed. In the secondary sintering process, a part of the optional M source is first mixed evenly with the source of other elements, and sintered, and then the remaining part of the M source is added and sintered after cooling and crushing; or all the optional M sources are mixed evenly with the source of other elements, and sintered, and then sintered again after cooling and crushing.

[0091] In some embodiments, sintering can be performed in an oxidizing atmosphere. Preferably, the oxidizing atmosphere is compressed air or oxygen.

[0092] In some embodiments, in the case of (i), the sintering temperature is in the range of 800-950° C., and / or the sintering time is in the range of 15-25 hours. As an example, the sintering temperature may be 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950° C., or in the range defined by any two of them, and / or the sintering time may be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 hours, or in the range defined by any two of them.

[0093] In some embodiments, for the secondary sintering, in the case of (ii), the temperature of the first sintering is in the range of 800-950° C., and / or the sintering time is in the range of 15-25 hours. As an example, the sintering temperature may be 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950° C., or in the range defined by any two of them, and / or the sintering time may be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 hours, or in the range defined by any two of them.

[0094] In some embodiments, for the secondary sintering, in the case of (ii), the temperature of the second sintering is in the range of 800-950° C., and / or the sintering time is in the range of 15-25 hours. As an example, the sintering temperature may be 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950° C., or in the range defined by any two of them, and / or the sintering time may be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 hours, or in the range defined by any two of them.

[0095] In some embodiments, for the secondary sintering, in the case of (ii), before the first sintering, 0-60 wt % of the optional M source is mixed with the source of other elements. For example, before the first sintering, 0 wt %, 10 wt %, 20 wt %, 30 wt %, 40 wt %, 50 wt %, or 60 wt % of the optional M source is mixed with the source of other elements, and then sintered. Then before the second sintering, the remaining 40-100 wt %, such as 100 wt %, 90 wt %, 80 wt %, 70 wt %, 60 wt %, 50 wt %, or 40 wt % is mixed with the product obtained by the first sintering, and then sintered.

[0096] In some embodiments, for the secondary sintering, in the case of (iii), the temperature of the first sintering is in the range of 800-950° C., and / or the sintering time is in the range of 15-25 hours. As an example, the sintering temperature may be 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950° C., or in the range defined by any two of them, and / or the sintering time may be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 hours, or in the range defined by any two of them.

[0097] In some embodiments, for the secondary sintering, in the case of (iii), the temperature of the second sintering is in the range of 800-950° C., and / or the sintering time is in the range of 15-25 hours. As an example, the sintering temperature may be 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950° C., or in the range defined by any two of them, and / or the sintering time may be 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 hours, or in the range defined by any two of them.

[0098] After research, the inventors found that when the sintering temperature and / or sintering time are within the range specified by the present invention, the obtained layered oxide positive electrode material has excellent composition uniformity, there are no copper oxide or nickel oxide impurity peaks in the corresponding XRD spectrum, and the residual alkali content of the obtained layered oxide positive electrode material is low.

[0099] In some embodiments, the volume average particle size D of the NiMn precursor is v 50≥2×(the largest volume average particle size D among the copper source, the titanium source and the M source) v50). When the volume average particle size of the NiMn precursor satisfies the above relationship with the volume average particle size of the copper source, the titanium source and the M source, the composition of the positive electrode material is more uniform, there are no impurity peaks of copper oxide and nickel oxide in the XRD spectrum of the product, and the residual alkali content of the obtained layered oxide positive electrode material is reduced, thereby improving the electrochemical performance.

[0100] In some embodiments, the volume average particle size D of the copper source is v 50≤7.0μm, for example 1.0-4.5μm. As an example, the volume average particle size D of the copper source v 50 can be 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0 μm, or within the range defined by any two of them. When the volume average particle size of the copper source is within the above range, it is beneficial to make the composition of the obtained layered oxide positive electrode material more uniform, and / or further reduce the residual alkali content of the obtained layered oxide positive electrode material, thereby improving the electrochemical performance.

[0101] In some embodiments, the volume average particle size D of the sodium source is v 50≤100μm, for example D v 50≤80μm. As an example, the volume average particle size D of the sodium source v 50 may be 5, 10, 20, 30, 35, 40, 45, 55, 60, 80, 90, 100 μm, or a range defined by any two of them.

[0102] In some embodiments, the volume average particle size D of the titanium source or the M source is v 50≤4.0μm. As an example, the volume average particle size D of the titanium source or the M source v 50 may be 1.0, 2.0, 3.0, 4.0 μm, or a range defined by any two of them.

[0103] In some embodiments, the volume average particle size D of the NiMn precursor is v 50≥3×(the largest volume average particle size D of the titanium source and the M source) v 50).

[0104] In some embodiments, the Na source, Cu source, Ti source, and optional M source may be any Na, Cu, Ti, or M-containing compound known to those skilled in the art for preparing a positive electrode material for a sodium ion secondary battery. Preferably, the Na source, Cu source, Ti source, and optional M source as a metal may be selected from one or more of carbonates, bicarbonates, nitrates, acetates, oxalates, hydroxides, and oxides of the corresponding elements, respectively. As an example, the Na source may be one or more of an oxide, hydroxide, salt, etc. containing sodium. In one or more embodiments, the Na source may be one or more selected from the following compounds: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, and sodium oxide; the Cu source may be one or more selected from the following compounds: copper carbonate, copper nitrate, copper acetate, copper oxalate, copper hydroxide, and copper oxide; the Ti source may be one or more selected from the following compounds: titanium carbonate, titanium nitrate, titanium acetate, titanium oxalate, titanium hydroxide, and titanium oxide; when M includes Al, the Al source may be one or more selected from the following compounds: aluminum carbonate, aluminum nitrate, aluminum acetate, aluminum oxalate, aluminum hydroxide, and aluminum oxide; when M includes Ca, the Ca source may be selected from the following compounds When M contains Mg, the Mg source may be one or more selected from the following compounds: magnesium carbonate, magnesium nitrate, magnesium acetate, magnesium oxalate, magnesium hydroxide and magnesium oxide; and when M contains Fe, the Fe source may be one or more selected from the following compounds: iron carbonate, iron nitrate, iron acetate, iron oxalate, iron hydroxide and iron oxide; when M contains Si, the Si source may be selected from one or more of silicic acid, silicate and silicon oxide; when M contains B, the B source may be selected from one or more of boric acid and boron oxide; when M contains P, the P source may be selected from one or more of phosphoric acid, phosphorous acid and phosphorus oxide. Alternatively or additionally, part or all of the Cu source, Ti source and optional M source may also be a composite oxide or a composite hydroxide.

[0105] In the method of the present invention, the cooling, crushing and screening can be carried out by any suitable means known to those skilled in the art. For example, the cooling can be natural cooling, air cooling or water cooling. For example, the crushing can be air flow crushing or mechanical crushing.

[0106] The inventors found in their research that when the volume average particle size and sphericity of the NiMn precursor are within the specified range, the volume average particle size D of the NiMn precursor is v 50≥2×(the largest volume average particle size D among the copper source, the titanium source and the M source) v50), and in combination with the specified composition, sintering temperature, sintering time and other conditions, the composition of the obtained layered oxide positive electrode material can be more uniform, and there are no copper oxide impurity peaks and nickel oxide impurity peaks in the XRD spectrum, and / or the residual alkali content of the obtained layered oxide positive electrode material can be easily controlled to be low.

[0107] Positive electrode composition

[0108] A third aspect of the present invention provides a positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the layered oxide positive electrode material according to the first aspect of the present invention.

[0109] In addition to the layered oxide positive electrode material of the present invention, the positive electrode composition (for sodium ion secondary battery) may further include a conductive agent, a binder and any other substances that can be used by those skilled in the art as needed, such as a dispersant and an additive for improving stability.

[0110] In some embodiments, based on the dry weight of the positive electrode composition (for sodium ion secondary battery), the content of the layered oxide positive electrode material may be a common amount in the art, for example, 70-95 wt %, for example 80-90 wt %.

[0111] The type of conductive agent is not particularly limited, as long as it has the performance of enhancing the positive electrode conductivity and not adversely affecting the layered oxide positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As an example, the conductive agent used for the positive electrode composition (for sodium ion secondary battery) can be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0112] In some embodiments, based on the dry weight of the positive electrode composition (for sodium ion secondary battery), the content of the conductive agent may be a common amount in the art, for example, 1-10 wt %, for example, 2-5 wt %.

[0113] The binder is not particularly limited as long as it has the properties of enhancing the adhesion between the positive electrode active material particles and the adhesion to the current collector and does not adversely affect the performance of the layered oxide positive electrode material. Those skilled in the art can select according to actual needs. As an example, the binder for the positive electrode composition (for sodium ion secondary battery) can be selected from polyfluoroolefin binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives and styrene-butadiene rubber, acrylic resin, carboxymethyl cellulose, polyvinyl alcohol (PVA), etc. One or more.

[0114] In some embodiments, based on the dry weight of the positive electrode composition (for a sodium ion secondary battery), the content of the binder is 1-10 wt %, for example, 2-5 wt %.

[0115] The positive electrode composition may be in the form of a slurry, that is, it may further include a solvent. The positive electrode composition may also be in a dry form, that is, it does not include a solvent, for example, it may be in the form of a positive electrode active material layer disposed on a positive electrode current collector.

[0116] Sodium ion secondary battery

[0117] A fourth aspect of the present invention provides a sodium ion secondary battery. A sodium ion secondary battery generally includes a positive electrode, a negative electrode, a separator and an electrolyte.

[0118] In some embodiments, the sodium ion secondary battery may further include an outer package for encapsulating the electrode assembly and the electrolyte. For example, the outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc., or a soft package, such as a bag-type soft package, such as a soft package made of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0119] The shape of the sodium ion secondary battery is not particularly limited, and it may be cylindrical, square, or any other shape.

[0120] The sodium ion secondary battery can be prepared by a method commonly used in the art. For example, the positive electrode sheet, the negative electrode sheet and the separator can be made into a battery cell through a winding process or a lamination process, and then the electrolyte is injected.

[0121] positive electrode

[0122] The positive electrode (or positive electrode sheet) comprises a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising the positive active material composition of the third aspect of the present invention, for example in dry form. The positive electrode also forms an aspect of the present invention.

[0123] The positive electrode current collector is not particularly limited, and the positive electrode current collector commonly used by those skilled in the art may be used. As an example, the positive electrode current collector may be a metal foil such as aluminum foil, nickel foil, or a composite current collector. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), 1,3-propane sultone (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.

[0124] The positive electrode sheet can be prepared according to the method commonly used in the art.

[0125] For example, the positive electrode can be formed by uniformly dispersing a positive electrode active material, a conductive agent, and a binder in a solvent (eg, N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; coating the slurry on a positive electrode current collector, drying, and pressing.

[0126] Alternatively, the positive electrode can also be formed by uniformly dispersing the positive electrode active material, the conductive agent, and the binder in a solvent (e.g., N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; casting the positive electrode slurry on a separate carrier, drying, separating the obtained positive electrode film from the carrier and laminating it on a positive electrode current collector.

[0127] negative electrode

[0128] The negative electrode (or negative electrode plate) may be a metal sodium plate, or may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0129] The negative electrode current collector is not particularly limited, and the negative electrode current collector commonly used by those skilled in the art can be used. As an example, the negative electrode current collector can be a metal foil such as copper foil, or a composite current collector. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.

[0130] In some embodiments, the negative electrode active material may be an active material commonly used by those skilled in the art. For example, the negative electrode active material may be one or more of natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon-based materials, tin-based materials, lithium titanate, and metallic sodium. Among them, the silicon-based material may be one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys, and the tin-based material may be one or more of elemental tin, tin oxide compounds, and tin alloys.

[0131] In some embodiments, the negative electrode active material may be included in an amount of 70-95 wt %, for example 80-90 wt %, based on the total weight (dry weight) of the negative electrode active material layer.

[0132] In addition to the negative electrode active material, the negative electrode active material layer may further include a binder, a conductive agent and any other optional auxiliary agents such as a thickener.

[0133] There is no particular requirement for the negative electrode conductive agent. As an example, the conductive agent can be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0134] In some embodiments, the conductive agent may be present in an amount of 1 to 10 wt %, for example 2 to 5 wt %, based on the total weight (dry weight) of the negative electrode active material layer.

[0135] There is no special requirement for the negative electrode binder. As an example, the binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), styrene butadiene rubber (SBR), water-based acrylic resin and carboxymethyl cellulose (CMC).

[0136] In some embodiments, the binder may be present in an amount of 1 to 10 wt %, for example 2 to 5 wt %, based on the total weight (dry weight) of the negative electrode active material layer.

[0137] The negative electrode can be prepared according to a method commonly used in the art.

[0138] For example, the negative electrode can be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (such as N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; coating the negative electrode slurry on a negative electrode current collector, drying, and pressing.

[0139] Alternatively, the negative electrode can also be formed by uniformly dispersing the negative electrode active material and optional conductive agent, binder and thickener in a solvent (e.g., N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; casting the negative electrode slurry on a separate carrier, drying, separating the obtained negative electrode film from the carrier and laminating it on a negative electrode current collector.

[0140] Electrolytes

[0141] The electrolyte plays a role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte is not particularly limited and can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte, a gel electrolyte, and a liquid electrolyte (i.e., an electrolyte).

[0142] In some embodiments, the electrolyte is an electrolyte solution, which includes an organic aprotic solvent and an electrolyte sodium salt.

[0143] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0144] In some embodiments, the electrolyte sodium salt can be selected from one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroborate (NaBF6), sodium bis(trifluoromethylsulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium trifluoromethylsulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).

[0145] In some embodiments, the concentration of sodium ions in the electrolyte is 0.2 to 2 mol / L, for example, 0.5-1.0 mol / L.

[0146] In some embodiments, the electrolyte may further include additives, for example, additives that help negative electrode film formation or positive electrode film formation, and additives that can improve battery performance, such as additives that improve high or low temperature performance of the battery.

[0147] Diaphragm

[0148] The separator is not particularly limited, and a commonly used porous structure separator with electrochemical stability and chemical stability can be used, for example, it can be a single layer or multilayer film of one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. When a solid electrolyte is used, the separator can also be omitted.

[0149] use

[0150] The fifth aspect of the present invention provides the use of the sodium ion secondary battery according to the fourth aspect of the present invention in an energy storage device for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.

[0151] Those skilled in the art will appreciate that the sodium ion secondary battery of the fourth aspect of the present invention may also be used for other purposes. For example, the sodium ion secondary battery may be used as a power source or energy storage unit in a mobile device (e.g., a mobile phone, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, an electric bicycle, an electric scooter, etc.), an electric train, etc.

[0152] Example

[0153] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0154] 1. Preparation Example

[0155] Example 1

[0156] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=80μm), Ni 0.45 Mn 0.50 O2 (D v 50=3.9μm,Φ=0.91), CuO (D v 50=1.4μm)、TiO2 (D v 50=1.2μm)、Al2O3 (D v 50=1.2μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 950°C in an air atmosphere for 15 hours. After cooling and pulverizing, the layered oxide positive electrode material Na 0.935 (Cu 0.550 Ti 0.450 ) 0.150 (Ni 0.450 Mn 0.550 ) 0.800 Al 0.050 O 2.000 (i.e. Na 0.935 Cu 0.083 Ti 0.068 Ni 0.360 Mn 0.440 Al 0.050 O 2.000 ). The crystal phase, D v 50 The particle size, sphericity, tap density, etc. are listed in Table 1 (the same below).

[0157] Example 2

[0158] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v50=20μm), Ni 0.50 Mn 0.50 (OH)2 (D v 50=5.3μm,Φ=0.97), CuO (D v 50=2.0μm), TiO2(D v 50=1.2μm) process raw materials and mixed them evenly using a high-speed mixer. Then, the secondary sintering process was used to sinter the resulting mixture in a furnace at 800℃ for 15h in an air atmosphere. After cooling and crushing, the primary sintering product was obtained. Then, Fe2O3 (D v 50 = 1.2 μm) was added to the primary sintered product and mixed evenly. The resulting mixture was sintered in a furnace under air atmosphere at 800 ° C for 15 h. After cooling and pulverization, the layered oxide positive electrode material Na 0.980 (Cu 0.450 Ti 0.550 ) 0.200 (Ni 0.500 Mn 0.500 ) 0.700 Fe 0.100 O 2.000 (i.e. Na 0.980 Cu 0.090 Ti 0.110 Ni 0.350 Mn 0.350 Fe 0.100 O 2.000 ).

[0159] Example 3

[0160] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=80μm), Ni 0.33 Mn 0.67 CO3(D v 50=3.0μm,Φ=0.93), CuO (D v 50=1.3μm), TiO2(D v 50=0.9μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 920°C in an air atmosphere for 15 hours. After cooling and crushing, the layered oxide positive electrode material Na 0.664 (Cu 0.550 Ti 0.450 ) 0.010 (Ni 0.330 Mn 0.670 ) 0.990 O 2.000 (i.e. Na 0.664 Cu0.006 Ti 0.005 Ni 0.327 Mn 0.663 O 2.000 ).

[0161] Example 4

[0162] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=20μm), Ni 0.50 Mn 0.50 (OH)2(D v 50=6.34μm, Φ=0.92), CuO (D v 50=2.0μm), TiO2(D v 50=1.2μm), CaO (D v 50=1.2μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 800°C in an air atmosphere for 20 hours. After cooling and crushing, the layered oxide positive electrode material Na 1.000 (Cu 0.500 Ti 0.500 ) 0.200 (Ni 0.500 Mn 0.500 ) 0.780 Ca 0.020 O 1.990 (i.e. Na 1.000 Cu 0.100 Ti 0.100 Ni 0.390 Mn 0.390 Ca 0.020 O 1.990 ).

[0163] Example 5

[0164] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=10μm), Ni 0.40 Mn 0.60 (OH)2(D v 50=8.70μm, Φ=0.94), CuO (D v 50=4.2μm), TiO2(D v 50=2.3μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 900°C in an air atmosphere for 15 hours. After cooling and crushing, the layered oxide positive electrode material Na 0.840 (Cu 0.500 Ti 0.500 )0.200 (Ni 0.400 Mn 0.600 ) 0.800 O 2.000 (i.e. Na 0.840 Cu 0.100 Ti 0.100 Ni 0.320 Mn 0.480 O 2.000 ).

[0165] Example 6

[0166] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=10μm), Ni 0.35 Mn 0.65 (OH)2(D v 50=12.00μm, Φ=0.91), CuO (D v 50=6.0μm), TiO2(D v 50=3.8μm)、MgO (D v 50=3.6μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 850℃ for 18h in an air atmosphere. After cooling and crushing, the layered oxide positive electrode material Na 0.782 (Cu 0.520 Ti 0.480 ) 0.100 (Ni 0.350 Mn 0.650 ) 0.740 Mg 0.160 O 1.920 (i.e. Na 0.782 Cu 0.052 Ti 0.048 Ni 0.259 Mn 0.481 Mg 0.160 O 1.920 ).

[0167] Example 7

[0168] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=10 μm), Ni 0.50 Mn 0.50 (OH)2(D v 50=6.34μm, Φ=0.95), CuO (D v 50=2.0μm), TiO2(D v50=2.00μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 800°C in an air atmosphere for 24 hours. After cooling and crushing, the layered oxide positive electrode material Na 1.000 (Cu 0.500 Ti 0.500 ) 0.010 (Ni 0.500 Mn 0.500 ) 0.990 O 2.000 (i.e. Na 1.000 Cu 0.005 Ti 0.005 Ni 0.495 Mn 0.495 O 2.000 ).

[0169] Example 8

[0170] According to the stoichiometric ratio of the elements, weigh Na2CO3 (D v 50=10 μm), Ni 0.33 Mn 0.67 CO3(D v 50=3.0μm,Φ=0.93), CuO (D v 50=1.30μm), TiO2(D v 50=0.93μm)、MgO (D v 50=0.92μm), CaO (D v 50=0.90μm) process raw materials, and use a high-speed mixer to mix them evenly. Then use a primary sintering process to sinter the resulting mixture in a furnace at 800°C in an air atmosphere for 24 hours. After cooling and crushing, the layered oxide positive electrode material Na 0.730 (Cu 0.450 Ti 0.550 ) 0.050 (Ni 0.330 Mn 0.670 ) 0.780 (Mg 0.500 Ca 0.500 ) 0.170 O 1.915 (i.e. Na 0.730 Cu 0.023 Ti 0.028 Ni 0.257 Mn 0.523 Mg 0.085 Ca 0.085 O 1.915 .

[0171] Comparative Example 1

[0172] Except for adjusting the stoichiometric ratio of the Cu source so that b in the general formula is 0.570, other conditions are the same as those in Example 1 to obtain a layered oxide positive electrode material Na 0.941 (Cu 0.570 Ti 0.430 ) 0.150 (Ni 0.450 Mn 0.550 ) 0.800 Al 0.050 O 2.000 (i.e. Na 0.941 Cu 0.086 Ti 0.065 Ni 0.360 Mn 0.440 Al 0.050 O 2.000 ).

[0173] Comparative Example 2

[0174] Except for adjusting the stoichiometric ratio of the Cu source so that b in the general formula is 0.440, other conditions are the same as those in Example 2 to obtain a layered oxide positive electrode material Na 0.976 (Cu 0.440 Ti 0.560 ) 0.200 (Ni 0.500 Mn 0.500 ) 0.700 Fe 0.100 O 2.000 (i.e. Na 0.976 Cu 0.088 Ti 0.112 Ni 0.350 Mn 0.350 Fe 0.100 O 2.000 ).

[0175] Comparative Example 3

[0176] Except Ni 0.33 Mn 0.67 CO3 (D v 50=3.0µm, Φ=0.93) is replaced by Ni 0.32 Mn 0.68 CO3 (Dv50=3.0µm, Φ=0.93), except that c in the general formula is 0.320, other conditions are the same as those in Example 3 to obtain a layered oxide positive electrode material Na 0.645 (Cu 0.550 Ti 0.450 ) 0.010 (Ni 0.320 Mn 0.680 ) 0.990 O 2.000 (i.e. Na0.645 Cu 0.006 Ti 0.005 Ni 0.317 Mn 0.67 3O 2.000 ).

[0177] Comparative Example 4

[0178] Except Ni 0.50 Mn 0.50 (OH)2(D v 50=6.34μm, Φ=0.92) is replaced by Ni 0.51 Mn 0.49 (OH)2(D v 50=6.34μm, Φ=0.92), except that c in the general formula is 0.510, other conditions are the same as those in Example 4 to obtain a layered oxide positive electrode material Na 1.016 (Cu 0.500 Ti 0.500 ) 0.200 (Ni 0.510 Mn 0.490 ) 0.780 Ca 0.020 O 1.990 (i.e. Na 1.016 Cu 0.100 Ti 0.100 Ni 0.398 Mn 0.382 Ca 0.020 O 1.990 ).

[0179] Comparative Example 5

[0180] Except for adjusting the stoichiometric ratio of the Cu source and the Ti source so that x in the general formula is 0.210, the other conditions are the same as those in Example 5 to obtain the layered oxide positive electrode material Na 0.842 (Cu 0.500 Ti 0.500 ) 0.210 (Ni 0.400 Mn 0.600 ) 0.790 O 2.000 (i.e. Na 0.842 Cu 0.105 Ti 0.105 Ni 0.316 Mn 0.474 O 2.000 ).

[0181] Comparative Example 6

[0182] Except for adjusting the stoichiometric ratio of the Cu source and the Ti source so that x=0 and 1-xy=0.260 in the general formula, the other conditions were the same as those in Example 6 to obtain the layered oxide positive electrode material Na 0.778 (Ni 0.350 Mn 0.650 ) 0.740 Mg 0.260 O 1.870 (i.e. Na 0.778 Ni 0.259 Mn 0.481 Mg 0.260 O 1.870 ).

[0183] Comparative Example 7

[0184] Except for adjusting the stoichiometric ratio of the Ni source and the Mn source so that y=1 and x=0 in the general formula, the other conditions were the same as those in Example 7 to obtain a layered oxide positive electrode material Na 1.000 (Ni 0.500 Mn 0.500 ) 1.000 O 2.000 (i.e. Na 1.000 Ni 0.500 Mn 0.500 O 2.000 ).

[0185] Comparative Example 8

[0186] Except for adjusting the stoichiometric ratio of the Ni source and the Mn source so that y=0.690 in the general formula, the other conditions were the same as those in Example 2 to obtain a layered oxide positive electrode material Na 0.980 (Cu 0.450 Ti 0.550 ) 0.200 (Ni 0.500 Mn 0.500 ) 0.690 Fe 0.110 O 2.000 (i.e. Na 0.980 Cu 0.090 Ti 0.110 Ni 0.345 Mn 0.345 Fe 0.110 O 2.000 ).

[0187] Comparative Example 9

[0188] In addition to CuO(D v 50=2.0µm) is replaced by CuO(D v 50 = 3.2 μm), the other conditions were the same as those in Example 7 to obtain a layered oxide positive electrode material Na 1.000 (Cu0.500 Ti 0.500 ) 0.010 (Ni 0.500 Mn 0.500 ) 0.990 O 2.000 (i.e. Na 1.000 Cu 0.005 Ti 0.005 Ni 0.495 Mn 0.495 O 2.000 ).

[0189] Comparative Example 10

[0190] In addition to Ni 0.40 Mn 0.60 (OH)2 (D v 50=8.7μm, Φ=0.94) is replaced by Ni 0.40 Mn 0.60 (OH)2 (D v 50 = 8.7 μm, Φ = 0.88), other conditions were the same as those in Example 5 to obtain a layered oxide positive electrode material Na 0.840 (Cu 0.500 Ti 0.500 ) 0.200 (Ni 0.400 Mn 0.600 ) 0.800 O 2.000 (i.e. Na 0.840 Cu 0.100 Ti 0.100 Ni 0.320 Mn 0.480 O 2.000 ).

[0191] Comparative Example 11

[0192] Except that the sintering temperature and time were adjusted to 780°C and 25h respectively (the temperature and time of the first sintering and the second sintering were the same), the other conditions were the same as those in Example 2 to obtain a layered oxide positive electrode material Na 0.980 (Cu 0.450 Ti 0.550 ) 0.200 (Ni 0.500 Mn 0.500 ) 0.700 Fe 0.100 O 2.000 (i.e. Na 0.980 Cu 0.090 Ti 0.110 Ni 0.350 Mn 0.350 Fe 0.100 O 2.000 ).

[0193] Comparative Example 12

[0194] Except that the sintering temperature and time were adjusted to 950°C and 9h respectively (the temperature and time of the first sintering and the second sintering were the same), the other conditions were the same as those in Example 2 to obtain a layered oxide positive electrode material Na 0.980 (Cu 0.450 Ti 0.550 ) 0.200 (Ni 0.500 Mn 0.500 ) 0.700 Fe 0.100 O 2.000 (i.e. Na 0.980 Cu 0.090 Ti 0.110 Ni 0.350 Mn 0.350 Fe 0.100 O 2.000 ).

[0195] Comparative Example 13

[0196] Except for adjusting the stoichiometric ratio of Cu source and Ti source so that x=0.030, resulting in 1-xy<0, bx+cy=0.510, other conditions were the same as those in Example 7 to obtain a layered oxide positive electrode material Na 1.020 (Cu 0.500 Ti 0.500 ) 0.030 (Ni 0.500 Mn 0.500 ) 0.990 O 2.030 (i.e. Na 1.020 Cu 0.015 Ti 0.015 Ni 0.495 Mn 0.495 O 2.030 ).

[0197] Comparative Example 14

[0198] Except for adjusting the stoichiometric ratio of Ni and Mn sources so that y in the general formula is 0.750 and bx+cy=0.270, other conditions are the same as those in Example 8 to obtain a layered oxide positive electrode material Na 0.730 (Cu 0.450 Ti 0.550 ) 0.050 (Ni 0.330 Mn 0.670 ) 0.750 (Mg 0.500 Ca 0.500 ) 0.200 O 1.895 (i.e. Na0.730 Cu 0.023 Ti 0.028 Ni 0.248 Mn 0.503 Mg 0.100 Ca 0.100 O 1.895 ).

[0199] Crystal phase, XRD analysis results, residual alkali content, D v 50 The particle size, sphericity, tap density, etc. are listed in Table 1. Figure 4 The XRD spectra of the layered oxide positive electrode materials prepared in Examples 3, 5 and 6 of the present invention are presented. Figure 4 It can be seen that there is no copper oxide impurity peak or nickel oxide impurity peak in the XTD spectrum of the prepared layered oxide positive electrode material. Figure 5 The XRD spectra of the layered oxide positive electrode materials prepared in Examples 2 and 7 of the present invention and Comparative Examples 7, 9 and 11 are presented. Figure 5 It can be seen that copper oxide or nickel oxide peaks appear in the XRD spectra of Comparative Examples 7, 9 and 11.

[0200] 2. Evaluation Example

[0201] 1. XRD test method

[0202] The X-ray diffractometer (model Bruker D8 ADVANCE) was used to test (λ=1.54056 nm) using a copper target (Cu-Kα) (accelerating voltage 40 KV, current 40 mA), with a range of 10-80 degrees, a step size of 0.02 degrees, a time of 0.2, and a total duration of 712 seconds.

[0203] 2. Dv50 particle size test method

[0204] Use Malvern 3000 laser particle size analyzer for testing. Select lithium cobalt oxide as the standard substance and water as the dispersant, and set the following instrument test parameters: test time 10s, test number 3, shading 6~15%, stirring speed 2800r / min, ultrasonic mode on, power 50%. Click the laser particle size analyzer (Malvern 3000 laser particle size analyzer) to start the test, and then add the primary sintering product or positive electrode material to the sample pool, control the amount added to adjust the shading of the sample pool to 6~15%. The instrument automatically repeats the test 3 times, and the average value of the 3 tests is taken as the mean of the test results.

[0205] 3. Sphericity measurement method

[0206] SEM was performed as follows: HITACHI (S-4800) scanning electron microscope was used for testing, with an accelerating voltage of 10 kV, a magnification of 10k, and general morphology photography.

[0207] In the plane of the obtained SEM image, first determine the face center of one of the positive electrode material particles, then read the shortest diameter of the particle passing through the face center in the plane, and then read the longer diameter in the plane perpendicular to the shortest diameter, and take the ratio of the shortest diameter to the longer diameter as the sphericity of the particle. The sphericity of ≥10 positive electrode material particles is obtained in the same way. The data in Table 1 are the statistical averages of 25 positive electrode material particles. Then take the quantitative average of the obtained sphericity, which is the sphericity of the obtained positive electrode material.

[0208] Figure 1-3 The SEM images of the layered oxide positive electrode materials prepared in Example 1, Example 2 and Example 4 of the present invention are presented. Figure 1-3 It can be seen that the prepared positive electrode material has a high sphericity. Figure 2 The calculation method of the sphericity of the present invention is schematically presented. After calculation, the sphericity of the layered oxide positive electrode material prepared in Example 2 is 0.95. The sphericity of other examples and comparative examples is summarized in Table 1.

[0209] 4. Tap density measurement method

[0210] Weigh 25g of layered oxide positive electrode material into a standard measuring cylinder (volume 50ml, inner diameter 22mm), and vibrate the measuring cylinder using a vibrator. The vibration machine setting parameters are: stroke 3mm, vibration frequency 100 times / min, time 30min. Read the volume of the positive electrode material in the measuring cylinder after vibration, and divide the powder mass by the volume to get the tap density.

[0211] 5. Residual alkali test method

[0212] According to the mass ratio of layered oxide positive electrode material: ethanol (analytical grade, density 0.789g / ml) = 1:20, take an appropriate amount of positive electrode material (mass is recorded as b) and add it to the corresponding amount of ethanol. Stir it magnetically at a speed of 600±20r / min for 30min so that ethanol can fully dissolve NaOH and Na2CO3 on the surface of the material. Then filter the mixture to obtain a filtrate, and use an atomic absorption spectrophotometer (Hitachi ZA3000) to test the Na +The residual Na content of the material is calculated according to the following formula: residual Na content = (a*(20*b / 0.789)) / b = a*20 / 0.789 *1000 mg / kg (i.e. ppm). The result is converted into a percentage content to obtain the residual alkali content based on the total weight of the layered oxide positive electrode material.

[0213] 6. Manufacturing of button cells

[0214] The positive electrode material to be tested: SP (Swiss Super P high conductive carbon black): polyvinylidene fluoride (PVDF, purchased from SOLVAY PVDF5130)) glue (mass fraction 10%, solvent N-methylpyrrolidone (NMP)) was mixed at a mass ratio of 90:5:5 on a dry weight basis, and NMP was added to make a viscous glue. The glue was coated on an aluminum foil (thickness 16µm), and then baked in a vacuum drying oven at 120°C for 12h to obtain a positive electrode sheet (active material surface density 5mg / cm 2 ). A sodium metal sheet (Aladdin) was used as the counter electrode (thickness 300±50µm). A glass fiber (Waterman) was used as the separator (thickness 675µm), and a NaPF6 solution (solvent is a mixture of EC and DMC, volume ratio EC / DMC=1:1) (Alfa) with a sodium ion concentration of 1 mol / L was used as the electrolyte. A 2032 button cell was assembled in an Ar atmosphere protection glove box.

[0215] 6.1. Initial discharge specific capacity (gram capacity)

[0216] After the 2032 button cell is assembled, place the button cell at 25°C, charge it to 4.2V at 0.1C constant current, then discharge it to 2.3V at 0.1C constant current, and then let it stand for 5 minutes to record the discharge capacity. Repeat the test 3 times according to the above method. Calculate the average of the discharge capacity of the three tests, which is the initial discharge capacity test result.

[0217] 6.2. Cycle retention and rate performance

[0218] The test conditions for cycle retention and rate performance are the same as the test conditions for the initial discharge specific capacity described in 6.1 above, except for the following: the charge and discharge rate is changed to 1C. The initial discharge specific capacity at 1C rate is measured, and the discharge specific capacity after 70 cycles at 1C rate is obtained. It is required to stand for 5 minutes after each discharge cycle. The 70-cycle cycle retention rate is calculated (the discharge specific capacity at 70 cycles divided by the initial discharge specific capacity, multiplied by 100%). The initial discharge specific capacity at 1C rate is divided by the initial discharge specific capacity at 0.1C rate to obtain the 1C / 0.1C rate performance.

[0219] Unless otherwise specified, all the above data are based on the average value obtained from parallel testing of three batteries.

[0220] The results of the initial discharge specific capacity, cycle retention rate, and 1C / 0.1C rate performance of Examples 1 to 8 and Comparative Examples 1 to 14 are summarized in Table 2.

[0221] Table 1 Physical and chemical properties of positive electrode materials of Examples 1 to 8 and Comparative Examples 1 to 14

[0222] * : Comparative Examples 4-5 and 11 also contain other impurity peaks whose compositions cannot be determined.

[0223] It can be seen from Table 1 that the layered oxide positive electrode materials prepared in Examples 1-8 of the present invention have a high sphericity. No copper oxide or nickel oxide impurity peaks were found in the XRD spectra of the obtained layered oxide positive electrode materials, and the residual alkali content in the obtained layered oxide positive electrode materials was less than 0.65%.

[0224] Table 2 Electrochemical performance test results of Examples 1 to 8 and Comparative Examples 1 to 14

[0225] It can be seen from Table 2 that, compared with Comparative Examples 1-14, the layered oxide positive electrode materials prepared in Examples 1-8 of the present invention have good comprehensive performance in initial discharge specific capacity, rate performance and cycle performance.

[0226] Specifically, by comparing Examples 1-2 and Comparative Examples 1-2, it can be found that the difference between them is that the molar ratio of Cu in the sum of Cu and Ti in Examples 1-2 (corresponding to b in the aforementioned general formula) is 0.550 and 0.450, respectively, while the corresponding values ​​b in Comparative Examples 1-2 are 0.570 and 0.440, respectively. Example 1 (initial discharge capacity 164.55 mAh / g, 1C / 0.1C rate 90.25%, discharge capacity after 70 cycles of 133.21 mAh / g, 70-cycle retention rate 89.70%, hereinafter the various properties are arranged in the same order) and Example 2 (172.34 mAh / g, 90.04%, 139.50 mAh / g, 89.90%) are better than Comparative Example 1 (159.78 mAh / g, 85.33%, 122.73 mAh / g, 90.02%) and Comparative Example 2 (168.43 mAh / g, 87.23%, 115.85 mAh / g, 78.85%). This shows that when the molar ratio of Cu in the sum of Cu and Ti is within the range defined in the present invention, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance comprehensive performance.

[0227] Similarly, by comparing Examples 3-4 and Comparative Examples 3-4, it can be found that the difference between them is that the molar ratio of Ni in the sum of Ni and Mn in Examples 3-4 (corresponding to c in the aforementioned general formula) is 0.330 and 0.500, respectively, while the corresponding values ​​c in Comparative Examples 3-4 are 0.320 and 0.510, respectively. Example 3 (88.35 mAh / g, 98.87%, 83.26 mAh / g, 95.32%) and Example 4 (170.00 mAh / g, 90.10%, 140.18 mAh / g, 91.52%) have better comprehensive performance in terms of initial discharge specific capacity, rate performance and cycle performance than Comparative Example 3 (87.15 mAh / g, 95.42%, 71.25 mAh / g, 85.68%) and Comparative Example 4 (172.00 mAh / g, 91.20%, 126.65 mAh / g, 80.74%) (the cycle performance of Example 4 is significantly better than that of Comparative Example 4). This shows that when the molar proportion of Ni in the sum of Ni and Mn is within the range defined in the present invention, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance comprehensive performance.

[0228] Similarly, by comparing Example 5 and Example 7 and Comparative Example 5 and Comparative Example 7, it can be found that the difference between them is that the sum of Cu and Ti in Example 5 and Example 7 (corresponding to x in the aforementioned general formula) is 0.200 and 0.010, respectively, while the corresponding values ​​x in Comparative Examples 5 and 7 are 0.210 and 0, respectively. Example 5 (162.73 mAh / g, 89.15%, 129.61 mAh / g, 89.34%) and Example 7 (171.35 mAh / g, 91.24%, 143.96 mAh / g, 92.08%) have better comprehensive performance in initial discharge specific capacity, rate performance and cycle performance than Comparative Example 5 (159.04 mAh / g, 86.43%, 125.39 mAh / g, 91.22%) and Comparative Example 7 (170.22 mAh / g, 89.63%, 122.04 mAh / g, 79.99%). This indicates that when the sum of the contents of Cu and Ti is within the range defined in the present invention, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance.

[0229] Similarly, by comparing Example 2 with Example 7 and Comparative Examples 7-8, it can be found that the difference between them is that the sum of Ni and Mn in Example 2 and Example 7 (corresponding to y in the aforementioned general formula) is 0.700 and 0.990, respectively, while the corresponding values ​​y in Comparative Examples 7-8 are 1.000 and 0.690, respectively. Example 2 (172.34 mAh / g, 90.04%, 139.50 mAh / g, 89.90%) and Example 7 (171.35 mAh / g, 91.24%, 143.96 mAh / g, 92.08%) have better comprehensive performance in terms of initial discharge specific capacity, rate performance and cycle performance than Comparative Example 8 (165.93 mAh / g, 89.32%, 122.02 mAh / g, 82.33%) and Comparative Example 7 (170.22 mAh / g, 89.63%, 122.04 mAh / g, 79.99%). This shows that when the sum of the contents of Ni and Mn is within the range defined in the present invention, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance comprehensive performance.

[0230] Similarly, by comparing Examples 7-8 and Comparative Examples 13-14, it can be found that the difference between them is that the sum of Cu and Ni in Examples 7-8 (corresponding to bx+cy in the aforementioned general formula) is 0.500 and 0.280, respectively, while the corresponding bx+cy in Comparative Examples 13-14 is 0.510 and 0.270, respectively. Example 7 (171.35 mAh / g, 91.24%, 143.96 mAh / g, 92.08%) and Example 8 (125.44 mAh / g, 97.32%, 115.23 mAh / g, 94.39%) have better comprehensive performance in terms of initial discharge specific capacity, rate performance and cycle performance than Comparative Example 13 (168.53 mAh / g, 92.13%, 143.02 mAh / g, 92.11%) and Comparative Example 14 (120.30 mAh / g, 89.65%, 102.69 mAh / g, 95.22%). This shows that when the sum of the contents of Cu and Ni is within the range defined in the present invention, it is beneficial to obtain improved initial discharge specific capacity, rate performance and cycle performance comprehensive performance.

[0231] In addition, by comparing Example 7 with Comparative Example 9, Example 5 with Comparative Example 10, and Example 2 with Comparative Examples 11-12, it can be found that by adjusting the maximum D V 50 Particle size and D of NiMn precursor V 50 The relative relationship between the particle size (Example 7 vs. Comparative Example 9), the sphericity of the NiMn precursor (Example 5 vs. Comparative Example 10), and the sintering temperature and time (Example 2 vs. Comparative Examples 11-12) are within the range defined by the present invention. The composition distribution of the prepared layered oxide positive electrode material is more uniform, there are no copper oxide or nickel oxide impurity peaks in the XRD spectrum, and the residual alkali content of the prepared layered oxide positive electrode material is low, which is conducive to obtaining improved initial discharge specific capacity, rate performance and cycle performance comprehensive performance.

[0232] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the inventive concept of the present invention, improvements can be made to the present invention, but these all belong to the protection scope of the present invention.

Claims

1. A layered oxide positive electrode material, the general formula of which is: So a (Cu b Tea 1-b ) x (Ni c Mr 1-c ) y M 1-x-y O d Wherein 0.65≤a≤1.00, preferably 0.75≤a≤1.00, preferably 0.80≤a≤1.00, more preferably 0.95≤a≤1.00; 0.45≤b≤0.55, preferably 0.45≤b≤0.50; 0.33≤c≤0.50, preferably 0.35≤c≤0.50, preferably 0.40≤c≤0.50, more preferably 0.45≤c≤0.50; 1.60≤d≤2.40; 0<x≤0.20, 0.70≤y<1.00, more preferably 0. 78≤y≤0.99, and 0.80≤x+y≤1.00, preferably 0.90≤x+y≤1.00, more preferably 0.98≤x+y≤1.00; M is selected from one or more of Fe, Mg, Zr, Zn, Al, Ca, Li, Ba, V, Cr, Mo, Co, Bi, B, Si, and P, preferably one or more of Fe, Co, Mg, Ba, Mo, Zr, Al, Ca, B, and P, and the values ​​of the subscripts of the elements in the general formula are selected so that the general formula satisfies the valence balance; and wherein 0.28≤bx+cy≤0.50, preferably 0.40≤bx+cy≤0.50, more preferably 0.44≤bx+cy≤0.50, The XRD spectrum of the layered oxide positive electrode material does not contain copper oxide impurity peaks and nickel oxide impurity peaks; The sphericity of the layered oxide positive electrode material is Φ≥0.85; and Wherein, based on the total weight of the layered oxide positive electrode material, the residual alkali content of the layered oxide positive electrode material is ≤0.65%, preferably ≤0.50%, and more preferably ≤0.30%.

2. The layered oxide cathode material according to claim 1, wherein bx / cy is in the range of 0.010-0.350, preferably 0.010-0.320, more preferably 0.010-0.

260.

3. The layered oxide positive electrode material according to claim 1 or 2, wherein 0.005≤bx / (1-c)y≤0.300, preferably 0.010≤bx / (1-c)y≤0.

260.

4. The layered oxide positive electrode material according to any one of claims 1 to 3, wherein one or more of the following are satisfied: bx is in the range of 0.005-0.100; cy is in the range of 0.250-0.500, preferably 0.320-0.500, preferably 0.350-0.500, more preferably 0.390-0.500; (1-b) x is in the range of 0.005-0.110, more preferably 0.005-0.100; or (1-c) y is in the range of 0.350 to 0.700, preferably 0.350 to 0.500, more preferably 0.390 to 0.

500.

5. The layered oxide positive electrode material according to any one of claims 1 to 4, wherein the tap density of the layered oxide positive electrode material is 1.80-2.10 g / cm 3 , preferably 1.90-2.10 g / cm 3 within the range. 6 . The layered oxide positive electrode material according to claim 1 , wherein the layered oxide positive electrode material has a sphericity Φ≥0.

90.

7. The layered oxide positive electrode material according to any one of claims 1 to 6, wherein the volume average particle size D of the layered oxide positive electrode material is v 50 is in the range of 3.0-15.0 μm, preferably 4.0-14.0 μm, more preferably 6.0-8.0 μm.

8. The layered oxide positive electrode material according to any one of claims 1 to 7, wherein the layered oxide positive electrode material is a P2 phase or an O3 phase, or a mixed phase of a P2 phase and an O3 phase, preferably an O3 phase.

9. A method for preparing a layered oxide positive electrode material according to any one of claims 1 to 8, comprising the following steps: (1) Provide a NiMn precursor having a Ni / Mn molar ratio satisfying c / (1-c): a sphericity of Φ ≥ 0.90, and a volume average particle size D v 50 is 3.0-15.0 μm, wherein c has the meaning defined in claim 1; (2) Do any of the following: (i) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, and optionally cooling and crushing; (ii) mixing the sodium source, the NiMn precursor, the copper source, the titanium source, and a portion of the optional M source uniformly, and sintering at 800-950° C. for 15-25 hours, cooling and pulverizing the resulting product, and then adding the remaining portion of the optional M source, mixing uniformly, and sintering again at 800-950° C. for 15-25 hours, and optionally cooling and pulverizing; or (iii) mixing a sodium source, the NiMn precursor, a copper source, a titanium source, and an optional M source, and sintering the mixture at 800-950° C. for 15-25 hours, cooling and crushing the resulting mixture, and sintering the mixture again at 800-950° C. for 15-25 hours, and optionally cooling and crushing the mixture, wherein Na, Ni, Mn, Cu, Ti and optionally M conform to the stoichiometric ratio defined in claim 1, and wherein the volume average particle size D of the NiMn precursor is v 50≥2×(the largest volume average particle size D among the copper source, the titanium source and the M source) v 50).

10. The method according to claim 9, wherein one or more of the following is satisfied: The volume average particle size D of the sodium source v 50≤100μm, for example D v 50≤80μm; The volume average particle size D of the titanium source or the M source v 50≤4.0μm; The volume average particle size D of the NiMn precursor v 50≥3×(the largest volume average particle size D of the titanium source and the M source) v 50).

11. The method according to any one of claims 9 to 10, wherein The Na source is one or more compounds selected from the following: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide and sodium oxide; The NiMn precursor is selected from one or more of the following compounds: NiMn hydroxide, NiMn oxide, NiMn carbonate, wherein the stoichiometric ratio of Ni to Mn is c / (1-c), wherein c has the meaning defined in claim 1; The Cu source is one or more selected from the following compounds: copper carbonate, copper nitrate, copper acetate, copper oxalate, copper hydroxide and copper oxide; The Ti source is one or more selected from the following compounds: titanium carbonate, titanium nitrate, titanium acetate, titanium oxalate, titanium hydroxide and titanium oxide; The metal source M is selected from one or more of the following compounds: carbonates, nitrates, acetates, oxalates, hydroxides and oxides; For example, when M comprises Al, the Al source is one or more selected from the following compounds: aluminum carbonate, aluminum nitrate, aluminum acetate, aluminum oxalate, aluminum hydroxide and aluminum oxide; When M comprises Ca, the Ca source is one or more compounds selected from the group consisting of calcium carbonate, calcium nitrate, calcium acetate, calcium oxalate, calcium hydroxide and calcium oxide; When M comprises Mg, the Mg source is one or more selected from the group consisting of magnesium carbonate, magnesium nitrate, magnesium acetate, magnesium oxalate, magnesium hydroxide and magnesium oxide; When M comprises Fe, the Fe source is one or more compounds selected from the group consisting of iron carbonate, iron nitrate, iron acetate, iron oxalate, iron hydroxide and iron oxide; When M comprises B, the source of B is one or more compounds selected from the group consisting of: boric acid and boron oxide; When M comprises Si, the Si source is one or more compounds selected from the group consisting of silicic acid, silicate esters and silicon oxide; and When M comprises P, the P source is one or more compounds selected from the group consisting of phosphoric acid, phosphorous acid and phosphorus oxide. 12 . A positive electrode composition, which is a positive electrode composition for a sodium ion secondary battery, comprising the positive electrode material according to claim 1 . 13 . A sodium ion secondary battery comprising the positive electrode composition according to claim 12 .

14. Use of the sodium ion secondary battery according to claim 13 in energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.